Entrance Surface Dose for patient`s undergoing X-ray examinations at Sebha medical center "Libya" - Abdulla, Y. A.; Aljewaw, Osama B. (Iraqi Journal of Science, 2018)
Diagnostic X-ray is one of the ionizing radiation that plays an important role in medical examination. Despite its great benefit, it is considered the largest source of artificial radiation exposure to public. The aim of the study is to measure the entrance surface dose (ESD) of patients undergoing chest, lumber spine and knee X-ray examination using TLD-100. The mean Entrance surface dose of chest (PA), lumber spine (AP, LAT) and knee (AP, LAT) are 1.3mGy, 8.57mGy, 21.5mGy and 0.49mGy, 0.48mGy respectively. The ESDs measured were found to be higher than the published work.